2018
DOI: 10.1007/s10787-018-0494-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of ivy leaves dry extract: influence on transcriptional activity of NFκB

Abstract: EA 575 is an ivy leaves dry extract (DER 5-7.5:1, 30% ethanol) used against diseases of the lower respiratory tract associated with productive cough. EA 575 improves symptoms associated with chronic inflammatory bronchial conditions. Compared to its bronchospasmolytic and secretolytic properties, the anti-inflammatory effects of EA 575 are mostly untried. Therefore, we addressed the question of whether the anti-inflammatory effect of EA 575 is due to an impact on the NFκB pathway. NFκB nuclear translocation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
1
11
0
9
Order By: Relevance
“…Up to now, plenty of studies have suggested that the increase of IKKα/β expression could reduce the release of NF-κB, which can induce the transcription of different cytokines in the nucleus. 64 Previous experiments have also confirmed that the activation of the NF-кB signaling pathway is one of the important factors in the SARS-CoV-2-induced inflammatory storm 65 ; therefore, we inferred that inhibiting the activity of the NF-кB signaling pathway is a mechanism of PDL for COVID-19 treatment. But in this work, we also found that the top active ingredients of PDL had no significant effects on the expression of ERK1/2, Akt, and JNK, which were the top targets of PDL according to the results of network pharmacology analysis.…”
Section: Discussionsupporting
confidence: 56%
“…Up to now, plenty of studies have suggested that the increase of IKKα/β expression could reduce the release of NF-κB, which can induce the transcription of different cytokines in the nucleus. 64 Previous experiments have also confirmed that the activation of the NF-кB signaling pathway is one of the important factors in the SARS-CoV-2-induced inflammatory storm 65 ; therefore, we inferred that inhibiting the activity of the NF-кB signaling pathway is a mechanism of PDL for COVID-19 treatment. But in this work, we also found that the top active ingredients of PDL had no significant effects on the expression of ERK1/2, Akt, and JNK, which were the top targets of PDL according to the results of network pharmacology analysis.…”
Section: Discussionsupporting
confidence: 56%
“…На думку Janka Schulte Michels і співавт. [25], компоненти екстракту листя плюща звичайного підвищують стабільність комплексу фактора транскрипції NF-κB із його інгібуючим фактором IκBα, що перешкоджає ядерній транслокації фактора транскрипції NF-κB і, як наслідок, індукції транскрипції прозапальних генів. Компоненти екстракту листя плюща звичайного перешкоджають або гальмують продукцію TNF-α і IL-6.…”
Section: таблиця 2 динаміка вираженості клінічних проявів (за шкалоюunclassified
“…Протизапальний ефект екстракту плюща доведений в експериментальних дослідженнях [23,25,29], а його виявлення пов'язують з наявні стю сапонінів, дубильних речовин, ефірних олій.…”
Section: оя міщенкоunclassified